Evaluation of teacher professional development program: A review of pre-service English teacher professionalism - Nurjanah, Lailatul; Wicaksono, Bayu Hendro; Andini, Thathit Manon; Effendi, Muhammad Idris (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The growing need for proficient educators has driven the government to establish extensive Pre-service Teacher Professional Development Programs. This research examined the implementation of the English Language Pre-service Teacher Professional Development Program at Universitas Muhammadiyah Malang. Employing a field research approach, this qualitative study utilized the CIPP (Context, Input, Process, and Product) model to analyze the program's effectiveness. The study yielded descriptive data, shedding light on the program's impact on participants' professionalism. The findings revealed a significant enhancement in the participants' professional competencies. This improvement is evident in their expanded knowledge of pedagogical content, as well as their heightened skills in preparing all facets related to the English language teaching (ELT) process. This encompasses the creation of ELT materials, instructional media, the utilization of diverse teaching, and school administrative management. The significance of this research lies in its contribution to the ongoing discourse on teacher professional development in the context of English language education. The study's insights could inform educational policymakers, curriculum designers, and teacher training institutions about the strengths and areas of improvement within the program. This research aimed to enrich the quality of English language education and foster the growth of proficient and dedicated educators.